Ações afirmativas na educação pública superior : análise de resultados de uma turma de cotistas do curso de administração da UFES - Pereira, Luciana Fernanda Puppin (2015)
Taking the specific case of the quota in public higher education, the aim of this study was to analyze the effectiveness of the quota program in groups who entered the Management Course at Universidade Federal do Espírito Santo, comprising how the school career of the quota student from this course was developed and if the quota program was effective. At first we used a quantitative approach which consisted of the analysis of categories presented in the school history of the student, and in a second moment of the research, we used a qualitative approach, carried out through interviews with the students who had already graduated in order to understand the impact of the higher education in their professional and family life. Thus, from the quantitative approach the study showed that the majority of quote students present results similar to the results achieved by UFES in previus statistics, except for the rates of abandoning and dropout, that for the analyzed group is higher. Qualitative bias demonstrates entering both the work market and labor mobility, it also highlights the transformations that were incorporated in the lives of graduated students because of the quota, covering since the domain of tools and techniques to develop the work as well as the ability of perceiving good opportunities that arise, contributing to increase educational perspectives of friends and family.